Bringing creative teaching into the young learner classroom. - Cameron, Lynne, 1952-; McKay, Penny, ....- (Oxford : University Press, 2010)
Bringing creative teaching into the young learner classroom is a practical guide for teachers of 5-12 year olds to help you make an informed choice about using personalized ideas and activities to encourage language learning. The contents of the book include: Knowing and challenging your learners; Encouraging your students to learn; Going beyond the coursebook; Empowering your learners; Assessment Playing with the sounds of English; Bringing the real world into the classroom; Using make believe; Performance and metaphor for the teacher: Language and cultural contexts.
Keywords: Engels -- Didactiek